2020
DOI: 10.1175/bams-d-19-0011.1
|View full text |Cite
|
Sign up to set email alerts
|

VolKilau: Volcano Rapid Response Balloon Campaign during the 2018 Kilauea Eruption

Abstract: Capsule Summary A Rapid balloon deployment during the 2018 Kilauea eruption provides a unique set of in situ measurements to understand volcanic plume chemical and microphysical properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…However, at Volcano village, while concentrations of SO 2 gas and sulphate are both much lower than atsource (assumed to be caused by dilution of the plume by background atmosphere), SO 2 gas concentrations have decreased much more than sulphate (80% versus 10% of source concentration, respectively). This may be due to vertical stratification of S species in the plume 44 -if SO 2 is transported at higher altitudes than sulphate, we might expect SO 2 to be less concentrated at ground-level sampling stations. Beyond Volcano village SO 2 concentrations continue to decrease consistently, but from Pāhala onwards, sulphate concentrations begin to increase as processes of sulphur conversion increase the proportion of S present as sulphate in the plume (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at Volcano village, while concentrations of SO 2 gas and sulphate are both much lower than atsource (assumed to be caused by dilution of the plume by background atmosphere), SO 2 gas concentrations have decreased much more than sulphate (80% versus 10% of source concentration, respectively). This may be due to vertical stratification of S species in the plume 44 -if SO 2 is transported at higher altitudes than sulphate, we might expect SO 2 to be less concentrated at ground-level sampling stations. Beyond Volcano village SO 2 concentrations continue to decrease consistently, but from Pāhala onwards, sulphate concentrations begin to increase as processes of sulphur conversion increase the proportion of S present as sulphate in the plume (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The field campaigns were designed to capture the composition of the volcanic plume and the background atmosphere at, or near ground level, where populations are exposed. The characteristics of the plume may have been different at higher altitudes in the atmosphere, due to vertical stratification of the plume in the troposphere; in particular, SO 2 and other gas species have been observed to separate from PM 44 . Therefore, the plume sampled downwind is unlikely to represent the bulk plume composition integrated through the troposphere.…”
mentioning
confidence: 99%
“…The measurements in Fig. 1 established the LERZ eruption as an extreme AQ event, and recent studies have used satellite and in situ measurements (15)(16)(17) to explore air quality implications and plume dynamics during the eruption. For example, analysis of regulatory network data found that 24-h average PM 2.5 concentrations exceeded US Environmental Protection Agency (EPA) AQ thresholds eight times during the eruption in certain locations, compared to zero times during the previous 8 y (17).…”
Section: Significancementioning
confidence: 89%
“…be identified and rejected. This cloud clearing has been established previously for studies related to the UTLS region (Vernier et al, 2015(Vernier et al, , 2018. Contrary, for cloud investigation, the COBALD was used in combination with the Cryogenic…”
Section: Estimation Of Saturation Relative Humiditymentioning
confidence: 99%